A Qualitative Analysis of the Role of Sleep Disorders in Sports Injuries Among Competitive Athletes in Canada - Longo , Veronica; Gottschlich , Daniela; Turner , Sarah; Qiu , Haixin (International Journal of Sport Studies for Health, 2025)
Objective: This study aimed to explore how competitive athletes in Canada understand, experience, and cope with sleep-related challenges in relation to their injury histories.Methods: Using a qualitative approach, we conducted semi-structured interviews with 31 athletes aged 19 to 34, representing both individual and team sports. All participants had experienced at least one sports injury and reported issues with sleep. The interviews were analyzed in three stages—open, axial, and selective coding—allowing us to move from detailed personal accounts to broader thematic insights. Results: The analysis identified four interrelated themes. Disrupted Sleep Patterns captured athletes’ difficulties with initiating and maintaining sleep, commonly linked to stress, physical tension, and pre-sleep screen use. Emotional Burden of Sleep Loss highlighted the psychological toll of sleep disturbances, including heightened anxiety, irritability, and feelings of shame—particularly when performance declined. Heightened Injury Susceptibility reflected athletes’ perceptions that inadequate sleep contributed to greater injury risk and prolonged recovery. Finally, Systemic Barriers and Ineffective Coping pointed to a lack of institutional sleep education, cultural stigma surrounding rest, and reliance on unhelpful self-management strategies, which often compounded the problem. Conclusion: Sleep issues in elite athletes are not just about feeling exhausted—they reach into deeper layers of well-being. Poor sleep affects not only how athletes perform, but also how they feel, recover, and even how they define themselves. Hearing these experiences directly from athletes themselves reveals an urgent need for more compassionate and informed support systems—ones that include meaningful sleep education, accessible mental health care, and a cultural shift in sports that values rest and recovery just as much as effort and endurance.